Evaluation of the antimicrobial effects of Capsicum, Nigella sativa, Musa paradisiaca L., and Citrus limetta: A review - Bhatti, Sonia Abid; Hussain, Muhammad Hammad; Mohsin, Muhammad Zubair; Mohsin, Ali; Zaman, Waqas Qamar; Guo, Meijin; Iqbal, Muhammad Waheed; Siddiqui, Shahida Anusha; Ibrahim, Salam A.; Ur-Rehman, Saeed; Korma, Sameh A. (Frontiers in Sustainable Food Systems, 2022)
The extensive use of antibiotics and vaccines against microbial infections can result in long-term negative effects on humans and the environment. However, there are a number of plants that have antimicrobial effects against various disease-causing microbes such as bacteria, viruses, and fungi without negative side effects or harm to the environment. In this regard, four particular plants- Capsicum, Nigella sativa, Musa paradisiaca L., and Citrus limetta have been widely considered due to their excellent antimicrobial effect and ample availability. In this review, we discuss their antimicrobial effects due to the presence of thymoquinone, p-cymene, pinene, alkaloids, limonene, camphene, and melanin. These antimicrobial compounds disrupt the cell membrane of microbes, inhibit cellular division, and form biofilm in bacterial species, eventually reducing the number of microbes. Extraction of these compounds from the respective plants is carried out by different methods such as soxhlet, hydro-distillation, liquid-liquid extraction (LLE), pressurized liquid extraction (PLE), solid-phase extraction (SPE), supercritical fluid extraction (SFE), pulsed electric field (PEF), microwave-assisted extraction (MAE), enzyme-assisted extraction (EAE), ultrasound-assisted extraction (UAE), and high-voltage electrical discharge. Suitable selection of the extraction technique highly depends upon the associated advantages and disadvantages. In order to aid future study in this field, this review paper summarizes the advantages and disadvantages of each of these approaches. Additionally, the discussion covers how antimicrobial agents destroy harmful bacteria. Thus, this review offers in-depth knowledge to researchers on the antibacterial properties of Capsicum, Nigella sativa, Musa paradisiaca L. peels, and Citrus limetta.